Determinants Of Job Performance Among Physicians In Public Hospitals In Iraq - Kadhim Alwali, Joather Abduljaleel (2022)
One of the main objectives of any working professional, be it a manager or an employee, is to deliver high job performance and to encourage his fellow peers, teams, and co-workers to do the same. Hence, the concept of job performance is an important building block in management. Job performance is a widely used in management, organizations rarely address what it really is, and in which areas of organizational practice it becomes important. In the effort to contribute to this issue, this study investigates the impact of compensation systems, training and development, information sharing, supervisory support, employees’ dynamic capabilities, emotional conflict, humble leadership, and creative self-efficacy towards innovative work behaviour among physicians in the public hospitals of Iraq.